PENGARUH KEPEMIMPINAN, DUKUNGAN ORGANISASI DAN KETERLIBATAN KERJA TERHADAP KINERJA SEKRETARIAT KOMISI PEMILIHAN UMUM PROVINSI SULAWESI TENGGARA - Farista Septiana; Adnan Hakim; Eliyanti Mokodompit; Laode Asfahyadin Aliddin; Muh. Taufik; Enny Wati (Jurusan Manajemen FEB UHO, 2024)
This research aims to determine the influence of leadership, organizational support, and work involvement on the performance of the Southeast Sulawesi Provincial General Election Commission Secretariat. The population of this research is all employees of the General Election Commission Secretariat of Southeast Sulawesi Province, totaling 39 people who have the status of State Civil Apparatus. The analysis used is quantitative analysis using Multiple Linear Regression Analysis. The research results show that; (1) Leadership, organizational support and work involvement have a positive and significant effect on the performance of the Southeast Sulawesi Provincial General Election Commission Secretariat; (2) Leadership reflected through directive leadership, supportive leadership, participative leadership, results-oriented leadership, instructive behavior, consultative behavior and delegative behavior has a positive and significant effect on the performance of the Southeast Sulawesi Provincial General Election Commission Secretariat; (3) Organizational support has a positive and significant effect on the performance of the Southeast Sulawesi Provincial General Election Commission Secretariat; (4) Work involvement has a positive and significant effect on the performance of the Southeast Sulawesi Provincial General Election Commission Secretariat.